الأمن السيبراني - الدام, محمد (University of Eloued جامعة الوادي, 2023)
أدى التحول الرقمي و الإعتماد المت ا زيد على تكنولوجيا المعلومات و الإتصال الذي يشهده العالم إلى بروز مفاهيم جديدة منها الفضاء السيب ا رني، و الذي تتم فيه جميع التفاعلات الرقمية. حيث شهد الفضاء السيب ا رني ت ا زيد عدد الهجمات السيب ا رنية بشكل كبير و مستمر، نظ ا ر لتعدد و إختلاف أشكال الج ا رئم السيب ا رنية، مما إستدعى ضرورة و جود ضمانات أمنية ضمن تحمي الفضاء السيب ا رني من الج ا رئم السيب ا رنية، تبورت بشكل أساسي في ظهور الامن السيب ا رني الذي أصبح يشكل جزءا أساسيا لمكافحة الج ا رئم السيب ا رنية على المستوى الوطني و الدولي.The digital transformation and the increasing dependence on information and communication technologies witnessed by the world have led to the emergence of new concepts, including cyberspace, which all digital interactions take place in. The cyberspace has witnessed a significant and continuous increase in the number of cyber-attacks, due to the multiplicity and variety of forms of cybercrimes, which necessitated the necessity and existence of security guarantees within the protection of cyberspace from cybercrimes, mainly manifested in the emergence of cyber security, which has become an essential part of the fight against cybercrimes at the national and international levels.
مذكرة ماستر
Keywords: الأمن السيب ا رني، الفضاء السيب ا رني، الج ا رئم السيب ا رنية، آليات مكافحة الج ا رئم السيب ا رنية; cyber security, cyber space, cyber-crimes, Mechanisms for combating cybercrime.